Comprehensive ability evaluation and trend analysis of patients with malignant intracranial tumors in the perisurgery period. Issue 11 (23rd September 2021) - Wang, Yaning; Chen, Wenlin; Yang, Tianrui; Zhao, Binghao; Zhou, Lizhou; Kong, Ziren; Wang, Yuekun; Dai, Congxin; Wang, Yu; Ma, Wenbin
Abstract: Introduction: Prognostic situations differ in patients with malignant intracranial tumors. We focused on the quality of life, ability of daily living, and cognitive function of patients in the perisurgery period and investigated the correlation between them and the prognosis of patients. Materials and Methods: Patients with malignant intracranial tumors admitted to Peking Union Medical College Hospital from May 2018 to August 2020 for surgery were included. The evaluations were performed 6 times in the perisurgery period. The questionnaires for assessment included QLQ‐C30, ADL, and so forth. Results: A total of 165 patients were included (115 glioma and 50 brain metastases). Patients had their worst performance at the 7‐day postsurgical assessment (EORTC QLQ‐C30, ADL, HAD‐D, Frail Scale, MMSE, MoCA, CSHA‐FI, and NANO) and recovered at the 1‐month postsurgical assessment ( p  < .05). Patients with left‐sided tumors had signiﬁcantly worse cognitive function than patients with right‐sided tumors before surgery and at 7 days, 1 month, and 6 months after surgery ( p  < .05). The scores of QLQ‐C30 and QLQ‐BN20 at 1 month, 3 months, 6 months, and 1 year after surgery were used to reflect the prognosis, and the preoperative MoCA, NANO, CCI, CSHA‐FI, and HAD score might predict the quality of life and nutrition status after operation. Conclusion: The quality of life and daily living ability of patients with malignant intracranial tumors decreased significantly 7 days after the surgery but recovered 1 month after the surgery. Patients with left hemisphere lesions had a worse cognitive function, while the ADL is associated with short‐term prognosis. The comprehensive evaluation of the perisurgical period can indicate the prognosis of patients and further guide clinical decision‐making. Abstract : Our research includes 165 patients with malignant intracranial brain tumor. It mainly focuses on the comprehensive assessments in the perisugery period in order to find the relationship between the results of the assessments and the outcomes of patients. We hope that the conclusion of this research can help clinical workers to treat patients in a more precise and effective way.